RIWAYAT KEKURANGAN ENERGI KRONIS (KEK) PADA IBU DAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS TURIKALE - Miftahul Jannah; Nadimin Nadimin (Media Kesehatan Politeknik Kesehatan Makassar, 2021)
Chronic Energy Deficiency (KEK) is a condition of experiencing malnutrition, especially in energy and protein that lasts a long time, causing health problems for pregnant women. Intrauterine Growth Retardation (IUGR) occurs due to nutritional deficiency where protein restriction causes growth retardation in the fetus. The adaptive responses that cause malnutrition occurring in utero has long-term consequences associated with adverse developmental health for both mother and child. The purpose of this research was to know the relationship of history of KEK in Mothers with Stunting Incidence in Toddlers in the Work Area of the Turikale Health Center, Maros Regency. This research is an analytical observational study with a cross sectional study design carried out in Pettuadae Village, Turikale District, Maros Regency in June 2021. There are two variables in this study, namely the independent variable, history of KEK and the dependent variable stunting. The collection of data on the history of KEK in mothers was obtained from the Maternal and Child Health (KIA) book and stunting data using secondary data sourced from the EPPGBM big data in February 2021 for 37 children. The population in this study were all 37 stunted children in Pettuadae Village, Turikale District, Maros Regency. The sample uses total sampling. Univariate data analysis to calculate frequency distribution and bivariate analysis using chi square test using SPSS 18 software. There is a relationship between the history of maternal constipation and the incidence of stunting in toddlers. It is expected that pregnant women will increase their nutritional needs during pregnancy so that they can avoid the occurrence of stunting in children and who want to conduct similar research, it is better to discuss other risk factors related to stunting in children and use a larger sample size. Keywords: Dietary habit, KEK, Stunting